Mpox gastrointestinal manifestations: a systematic review - Rahul Ramakrishnan; Atira Shenoy; Ranganathan Madhavan; Damon Meyer (BMJ Open Gastroenterology)
Introduction Mpox is a viral infection caused by the monkeypox virus, a member of the Poxviridae family and Orthopoxvirus genus. Other well-known viruses of the Orthopoxvirus genus include the variola virus (smallpox), cowpox virus and vaccinia virus. Although there is a plethora of research regarding the dermatological and influenza-like symptoms of mpox, particularly following the 2022 mpox outbreak, more research is needed on the gastrointestinal (GI) effects.Objectives This systematic review is to outline the GI manifestations of the monkeypox virus.Methods The authors conducted this systematic review using guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. A search was conducted through the PubMed, EMBASE and MEDLINE databases from January 1958 to June 2023. The authors selected English language papers that discussed the GI symptoms in mpox patients. A manual search was also conducted in the reference sections of these publications for other relevant papers.Results 33 papers involving 830 patients were selected for this review. The GI manifestations in mpox patients are proctitis, vomiting, diarrhoea, rectal pain, nausea, tenesmus, rectal bleeding and abdominal pain. Although various papers explored transmission routes, one paper established a direct connection between anal-receptive sex transmission route and the development of a GI complication (proctitis). Another study reported that the mode of transmission could potentially impact the occurrence of GI symptoms and severity of the disease. The reviewed papers did not discover a relation between the severity of dermatological and influenza-like symptoms and the GI manifestations mentioned.Conclusion This systematic review confirms that GI manifestations are observed in mpox patients. GI symptoms of mpox are crucial for gastroenterologists and other healthcare professionals to recognise in order to address patient discomfort and further understand the pathophysiology of the virus.